2009
DOI: 10.1364/ol.34.003259
|View full text |Cite
|
Sign up to set email alerts
|

Saddle solitons: a balance between bi-diffraction and hybrid nonlinearity

Abstract: We demonstrate self-trapping of light by simultaneously compensating normal and anomalous (saddleshaped) diffractions with self-focusing and self-defocusing hybrid nonlinearity in optically induced ionic-type photonic lattices. Innovative two-dimensional gap solitons, named "saddle solitons," are established, whose phase and spectrum characteristics are different from all previously observed spatial solitons. © 2009 Optical Society of America OCIS codes: 190.6135, 190.5330, 350.4238. Despite the discovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Furthermore, with such hybrid nonlinearity, a new type of spatial gap solitons, namely, 'saddle' solitons, can be established. In fact, Hu et al observed such 'saddle' solitons by balancing the saddle-shaped bi-diffraction with hybrid focusing/defocusing in an optically induced 2D ionic-type lattice [253]. These 'saddle' solitons have a propagation constant residing in the Bragg reflection gap, but they differ from all previously observed solitons supported by a single focusing or defocusing nonlinearity.…”
Section: New Families Of Spatial Solitonsmentioning
confidence: 95%
“…Furthermore, with such hybrid nonlinearity, a new type of spatial gap solitons, namely, 'saddle' solitons, can be established. In fact, Hu et al observed such 'saddle' solitons by balancing the saddle-shaped bi-diffraction with hybrid focusing/defocusing in an optically induced 2D ionic-type lattice [253]. These 'saddle' solitons have a propagation constant residing in the Bragg reflection gap, but they differ from all previously observed solitons supported by a single focusing or defocusing nonlinearity.…”
Section: New Families Of Spatial Solitonsmentioning
confidence: 95%
“…Another type of nonlinearity is associated with the photorefractive response, where non-locality relates to the diffusion of light-induced carriers. In photorefractive media the nonlinear index well is not single-humped for a bell-shaped input and the transition from self-focusing to self-defocusing can be achieved via crystal rotation [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…According to the Floquet-Bloch theorem, beam propagation in photonic lattices can be analyzed from spatially extended Bloch waves as a complete orthogonal set of allowed eigenmodes of the lattice [2]. In uniform photonic lattices, localized modes characterized by Bloch waves are crucial for understanding the formation of spatial lattice solitons [7][8][9][10][11][12]. Recently, many intriguing linear and nonlinear phenomena have been reported in deformed or anisotropic lattices [5,12].…”
mentioning
confidence: 99%
“…Because of the intrinsic anisotropic nonlinearity [13,14], the light-induced photonic lattices possess high anisotropy, which can be tuned by the bias condition [3,11,12]. Under the illumination of the hexagonal lattice beam [see the background of Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation